Leaf litter mass loss rates and associated fauna of tree species commonly used in neotropical riparian reforestation (2014)
ABSTRACT: A signature of globalization is the prevalence of exotic trees along reforested urban and rural riparian zones in the Neotropics, but little is known about the instream processing of its leaf litter. In this study, leaf litter breakdown rates were measured during 35 days using mesh bags within a reference headwater stream for seven exotic and three native tree species commonly used in urban and rural reforestation. Artocarpus altilis, Schefflera actinophylla and Terminalia catappa scored the highest mass loss rates (>85 %; mean life: t50 <15 d), while Cecropia sp. and Cespedesia macrophylla (mass loss =36 and 15 %; t50 =58 and 172 d, respectively) scored the lowest rates. However, a broad range of rates was observed among the ten species studied. The carbon to phosphorus ratio (C:P) and toughness of the leaf litter were the best predictors of breakdown rates. However, these leaf properties were not correlated with the very low values of macroinvertebrates abundance and diversity, and the few morphs classified as shredders. Therefore physical rather than biological controls seem to best explain the observed variability of mass loss rates, and thus slow decomposing leaf litter species seems to provide a habitat rather than a food resource, particularly to collectors. This study suggests that riparian reforestation will propagate species-specific ecological influences on instream processes such as leaf litter processing depending on leaf quality properties, therefore ecosystem-wide influences should be considered for improving reforestation strategies. Future studies should test for differences in breakdown rates and colonization by macroinvertebrates relative for leaf litter species origin (native vs. exotic).